The Administrative Measures on Driving Behavior Point Deduction System - Kaewsai, Thakoon (Journal of MCU Phetchaburi Review, 2026)
This thesis aims to study the legal issues arising from the enforcement of the measure to delay the issuance of annual tax payment label under the Order of the Head of the National Council for Peace and Order No. 14/2560, as well as the measure to record the behavior points of licensed drivers who violate or fail to comply with traffic laws. The study found that there are problems concerning the deduction of driving behavior points and the delay in issuing annual tax payment stickers, which are not yet consistent with the principles of public law and the intent of the legislation. These issues affect the effectiveness of law enforcement, lead to a lack of public acceptance, and result in disputes between citizens and law enforcement officers. The researcher therefore proposes an amendment to the regulations concerning the criteria, procedures, and conditions of the driving behavior point recording system for licensed drivers, which were issued under the authority provided in Section 142/1, paragraph two, and Section 142/4 of the Land Traffic Act B.E. 2522 (1979), as amended by the Land Traffic Act (No. 12) B.E. 2562 (2019). By repealing the criteria and procedures for recording driving behavior points in cases where points are deducted for receiving a traffic ticket and failing to pay the fine without reasonable cause, as well as in cases where the driver cannot be identified and points are instead deducted based on the name appearing in the vehicle registration records as the legal owner under the vehicle law, or as the transport operator under the land transport law. In addition, Section 141/1 of the Land Traffic Act B.E. 2522 (1979), as amended by the Order of the Head of the National Council for Peace and Order No. 14/2560 on measures to enhance the efficiency of law enforcement under the Land Traffic Act, dated March 21, 2017, should also be repealed. To ensure that the enforcement of such legal measures is consistent with the principles of public law and the intent of the legislation, is effective, capable of promoting safer driving behavior, encourages respect for traffic laws, gains public acceptance, and prevents future disputes between citizens and law enforcement officers.